Fitorremediação - SOLDERA, Caroline; CAMPOS, Fabrício Oliveira de; DINIZ, Isabele Mello; SILVA, Leticia Pedroso da; CUSTODIO, Rebeca Hortiz (117, 2024)
Não possui.
Keywords: Cobre; Poluição; Fitorremediação; Ambiente e Saúde